THE MUSLIM WOMEN (PROTECTION OF RIGHTS ON MARRIAGE) ACT, 2019: AN INSUBSTANTIAL ADDITION TO THE REALM OF LAW - et. al., Ahmar Afaq (International Journal of Modern Agriculture, 2021)
The Muslim personal law governing the family law matters of Muslims in India has always been under a scrutiny with allegations of being gender discriminatory. At the core of these allegations have been divorce provisions in general and Instant Triple Talaq or Talaq-ul-Biddat in particular. The practice was set aside by the apex court in the case of Shayra Bano v. Union of India and was declared void and illegal by the Muslim Women (Protection of Rights on Marriage) Act, 2019. The Act further provides the punishment of imprisonment up to three years in case a husband indulges in the said practice. The Act is hailed by many for empowering the Muslim women and rescuing them from the injustice faced for centuries. On the other hand the Act is criticized labeling it froth, made in haste and capable of doing more harm than good to the Muslim women. Through the instant academic work an effort has been made to critically analyze the provisions of the said Act on various grounds like criminalizing a private conduct, quantum of punishment, subsistence allowance, custody of the child to substantiate that it is an insubstantial addition to the realm of law. The Act leading to the multiplicity (Shayara Bano v. Union of India and others, 2017) of laws has been reflected by discussing that the existing laws would have been enough to take care of the wrong doings of the pronouncement of Instant Triple Talaq after the decision of the apex court..